IMMU-14. ONCOLYTIC ADENOVIRUS DELTA-24-RGD ENGINEERED TO EXPRESS 4-1BBL AS A THERAPEUTIC APPROACH FOR DIPG. (9th November 2020) - Laspidea, Virginia; Puigdelloses, Montserrat; Martinez-Velez, Naiara; Garcia-Moure, Marc; Labiano, Sara; Ausejo, Iker; Patiño-García, Ana; Becher, Oren J; Jiang, Hong; Gupta, Sumit; Fueyo, Juan; Gomez-Manzano, Candelaria; et al.
Abstract: Despite the advances in our understanding of pediatric diffuse midline gliomas (DMG) they remain the leading cause of pediatric death caused by cancer. Our group has demonstrated that the administration of Delta-24-RGD in DIPG models is safe and therapeutically efficacious. An on-going clinical trial with this virus has proven to be safe for these patients. To further improve the anti-tumoral response of the virus, we armed Delta-24-RGD with 4-1BBL (Delta-24-ACT). 41BB is a costimulatory receptor that promotes the survival and expansion of activated T cells, and the generation and maintenance of memory CD8+ T cells. Here, we showed that in vitro Delta-24-ACT can infect and express 4-1BBL in murine and human DIPG cell lines. Importantly, 4-1BBL expression in DIPG cell lines was able to activate lymphocytes and increase their IFN-gamma production. In addition, Delta-24-ACT triggered immunogenic cell death in DIPG cell lines, as shown by the release of DAMPs such as ATP, HMGB1, Hsp90a and calreticulin translocation. Delta-24-ACT administration in orthotopic DIPG models was well tolerated and safe. We confirmed the expression of the ligand within the tumor. Moreover, using flow cytometry and multispectral immunohistochemistry we observed profound changes in the tumor microenvironment with an increase in the T-cell populations and a remodeling of the myeloid component before and after treatment. Functional studies showed no differences in lymphocytes isolated from mice treated splenocytes but uncovered TILS that showed a significantly increased in the production of IFN-gamma. Delta-24-ACT treatment of mice bearing orthotopic DIPG murine tumors resulted in a significant increase in the median survival and led to free of disease long-term survivors. In summary, Delta-24-ACT is a virus that builds in our clinical experience with Delta-24-RGD in DIPG patients going a step further to boost the antitumor effect of viral therapy while maintaining a safe profile.